Transformasi Pembelajaran Bahasa Indonesia dengan Menggunakan Model TEL (Techonolgy Enhanced Learning) untuk Meningkatkan Antusiasme dan Kolaborasi Siswa Kelas VIII di MTs Humaira Kota Bengkulu - Susanti, Median; Wediasti, Welti; Khermarinah, Khermarinah (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to explore the transformation of Indonesian language learning through the implementation of the TEL (Technology Enhanced Learning) model in enhancing the enthusiasm and collaboration of eighth-grade students at MTs Humaira, Bengkulu City. This research employs a descriptive qualitative method using observation, interviews, and documentation techniques. Data were collected over eight meetings involving one Indonesian language teacher, 19 students, and the principal as an observer. The findings indicate that six out of seven TEL indicators have been consistently applied, such as student-centered teaching, the use of digital platforms, and a flexible curriculum. The integration of technologies like Google Classroom, WhatsApp, and YouTube has proven to increase students' enthusiasm and collaboration. The learning environment became more interactive, engaging, and supportive of collaboration. The implementation of the TEL model has been effective in supporting a more interactive and collaborative Indonesian language learning process at MTs Humaira.